The Impact Of Communication Apprehension Levels On Objective Structured Clinical Examination Performance Among Medical Students - Ramli, Muhammad Rizaldi; Pamungkasari, Eti Poncorini; ., Maryani; Budiastuti, Veronika Ika (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: By definition, communication apprehension is the discomfort or nervousness felt when interacting or preparing to interact with others. OSCE, on the other hand, evaluates students' clinical skills through various simulated scenarios. Communication apprehension might impact students' clinical abilities assessed in OSCE, given that these skills also rely on effective communication.Aims: This research aims to explore how the level of communication anxiety correlates with students OSCE performance.Methods: This research involved 201 participants from the Faculty of Medicine at UNS. Data was gathered using the PRCA-24 questionnaire to gauge communication apprehension levels, alongside OSCE scores as secondary data. The relationship between these variables was examined using linear regression analysis.Results: At a significance level of α = 0.05, a significant correlation was found between communication apprehension and OSCE scores. This was supported by a p-value of 0.002 and a coefficient of determination (R squared) of 0.048.Conclusion: It was observed that communication apprehension levels had an impact on OSCE scores.